The The Effect of Caffeine Consumption on the Level of Anxiety Disorders in Medical Students - Angelica Salim; Gusbakti Rusip; I Nyoman Ehrich Lister; Suandy Suandy; Putri Handayani (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2025)
This study aimed to analyze the effect of caffeine consumption on anxiety levels in students. A quantitative cross-sectional design with an analytical survey approach was employed. Sampling was conducted using total sampling based on inclusion and exclusion criteria. Data were collected through a caffeine consumption frequency questionnaire and the Hamilton Anxiety Rating Scale (HARS), and analyzed using the Chi-Square test. The results showed that most respondents experienced mild anxiety. The most commonly consumed sources of caffeine were ready-to-drink coffee and green tea. Statistical analysis indicated a significant relationship between caffeine consumption and anxiety levels, both for coffee (p = 0.008) and tea (p = 0.029). These findings suggest that increased caffeine intake is associated with higher anxiety levels in students. Therefore, it is recommended that students limit their daily caffeine consumption to maintain sleep quality and emotional balance.